Some questions of social and cultural history of the region of Sétif in the nineteenth - kaouane, fares (Journal of Social Sciences and Humanities, 2020)
This article deals with some questions of social and cultural history of the region of Setif during the colonial period. Some of these issues are related to the social situation and movements of populations in the region and their health status. They also reveal the situation of the local community and its attitudes. It also reveals to us the practices of the colonial administration and some of its deputies and the advanced status of the Jews even before they acquired French nationality. Some zaouia documents also explore aspects of cultural life in the region, which are not mentioned in the sources and studies that have focused on this topic.